The Obsidian Industry At Bukit Tengkorak, Sabah, Malaysia. - Chia, Assoc Prof. Dr. Stephen, Ming Soon (1998)
In 1994-95, archaeological research was undertaken by a joint Centre for Archaeological Research Malaysia and Muzium Sabah team at Bukit Tengkorak, a Neolithic site in Semporna, Sabah (Figure l). Geologically, Bukit Tengkorak forms part of the rim of a 2 kilometer-wide volcanic crater, surrounded by numerous isolated hills and mountains, most of them representing sites of extinct volcanoes ranging from Pliocene to Quaternary in age (HD 'Tjia, personal communication, Kirk l962,Lee 1970).